How and when servant leadership promotes service innovation: A moderated mediation model. (October 2021) - Li, Fengyu; Liu, Bing; Lin, Weipeng; Wei, Xin; Xu, Zikun
Abstract: Based on social learning theory, the current study examined how and when servant leadership could promote employee service innovative behavior (SIB) in the hospitality setting. Survey data collected from 1021 service employees and their 229 direct supervisors at 54 hotels showed that servant leadership was positively related to employee SIB, and employee customer orientation mediated such effect. Results also showed that employee age moderated the effect of servant leadership on customer orientation, as well as the indirect effect of servant leadership on SIB via customer orientation, such that these effects were stronger for younger employees. Theoretical and practical implications are discussed.